Bimetal hybridization metasurface capable of realizing polarization selective absorption and adjustable and controllable immersion liquid

By adopting a bimetal hybrid superstructure structure and using the combination of bimetal hybrid layer, silver layer and insulating layer, the problems of insufficient polarization-related absorption contrast and unstable optical performance in the tuning process in the prior art are solved, and the infrared polarization with high contrast is selected perfect absorption and reflection, and flexible wavelength tuning capabilities are achieved.

CN119805636AActive Publication Date: 2025-04-11YANGTZE UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510121873.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-11
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high contrast polarization-related absorption and maintain the stability of optical performance during active tuning.

Method used

Using a bimetal hybrid superstructure structure, including a bimetal hybrid layer at the top, a silver layer at the bottom, and an insulating layer at the middle, the absorption peak wavelength is tuned by adjusting the cell period and using liquids with different refractive indices.

Benefits of technology

It achieves high-contrast infrared polarization selection perfect absorption and reflection, and can continuously tune the absorption peak wavelength in the near-infrared band range to maintain the stability of optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805636A_ABST
    Figure CN119805636A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetal hybridization super-structure surface capable of realizing polarization selective absorption and adjustable immersion liquid. The super-structure surface is composed of a double-metal hybridization layer, a silicon dioxide layer and a silver reflecting layer, wherein the double-metal hybridization layer is composed of an aluminum nanobelt and a titanium nanobelt. The bimetal hybridized metasurface can perfectly absorb incident light under x polarized light at a resonant wavelength and can realize specular reflection on the incident light under y polarized light, so that the bimetal hybridized metasurface has a relatively high extinction ratio. In addition, the absorption peak wavelength of the super-structure surface can be continuously and dynamically regulated and controlled by adjusting the unit period of the super-structure surface or utilizing an active tuning means of liquid infiltration. The bimetal hybridization super-structure surface provided by the invention can realize high-contrast polarization selective absorption, and has the advantages of simple structure, easiness in integration, dynamic adjustability and the like, so that the bimetal hybridization super-structure surface can be widely applied to practical application scenes such as novel optical polaroids, photoelectric detectors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metasurface optical technology, and in particular to a bimetallic hybrid metasurface that can realize polarization-selective absorption and immersion-controllable liquid. Background Art

[0002] Metasurface technology can achieve unprecedented control freedom of light on a subwavelength scale, which is reflected in various functions such as structural color, perfect absorption, beam steering, metaholography, emission control, etc. In these functional research fields, perfect absorbers based on metasurfaces constitute the basis of light control technology, which has a far-reaching impact on application fields such as photovoltaics, photodetection, optical filtering, and biomedical sensing. With the continuous deepening of micro-nano photonics research and the continuous advancement of technology, nanostructured metasurfaces have shown great potential in the field of light control, especially in multifunctional absorption. Metal-insulator-metal architecture, as a common structure for spectral manipulation of metasurfaces, has been widely studied through various physical principles (such as plasmon resonance, Fabry-Perot resonance, bound states in continuum, etc.) and applied to perfect absorption in different frequency bands. For example, a three-layer film of metal-insulator-metal structure can absorb light at a specific frequency, and its resonant wavelength can be precisely tuned by adjusting the thickness of the insulator layer.

[0003] Although many studies have focused on the dynamic perfect absorption of metasurfaces, how to achieve high-contrast polarization-dependent absorption and maintain the stability of optical performance during active tuning remains a key technical challenge that needs to be addressed urgently. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a bimetallic hybrid metasurface that realizes polarization-selective absorption and immersion-adjustable liquid, so as to overcome the deficiencies in the prior art in terms of whether the optical performance can be kept stable during high-contrast polarization-dependent absorption and tuning, and realize efficient, stable and flexibly tunable infrared polarization-selective perfect absorption function.

[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0006] In the first aspect, the present invention provides a bimetallic hybrid metasurface, which is based on a bimetallic hybrid layer-insulating layer-metal layer architecture; the bimetallic hybrid layer is located at the top, and the bimetallic hybrid layer is composed of a first metal nanobelt and a second metal nanobelt, the first metal nanobelt and the second metal nanobelt are infinitely extended along the y-axis, and the first metal nanobelt and the second metal nanobelt are arranged periodically along the x-axis. The metal layer is located at the bottom; the insulating layer is located between the top metal layer and the bottom metal layer.

[0007] In a preferred embodiment, the bimetallic hybrid metasurface that realizes polarization-selective absorption and immersion-adjustable liquid has a top metal layer composed of titanium nanoribbons and aluminum nanoribbons that are infinitely long along the y-axis. The synergistic effect of these two metal nanoribbons is the key to realizing the polarization-selective function.

[0008] The bottom of the bimetallic hybrid metasurface is a thick silver layer with a thickness of 100-120nm (preferably 100nm). In specific implementation, an appropriate thickness is selected to ensure the reflection of light. The silver layer can reflect the electromagnetic waves that pass through the middle layer back into the structure, increase the propagation path of the electromagnetic waves in the structure, and thus improve the absorption efficiency.

[0009] The insulating layer in the middle of the bimetallic hybrid metasurface is any one of silicon dioxide, aluminum oxide or organic glass (preferably a silicon dioxide layer), and the thickness is on a sub-wavelength scale. By changing the thickness of the insulating layer, the resonance frequency of the absorption device can be adjusted to the desired frequency band.

[0010] In a second aspect, the present invention provides a liquid-adjustable infrared polarization selective absorption device, comprising the above-mentioned bimetallic hybrid metasurface. The absorption peak wavelength of the x-polarized infrared light band can be adjusted by changing the metasurface unit period or immersing the metasurface in liquids with different refractive indices.

[0011] Furthermore, the application of the bimetallic hybrid metasurface that realizes polarization-selective absorption and immersion-adjustable liquid is as follows: the bimetallic hybrid metasurface can perfectly absorb and reflect x-polarized infrared light and y-polarized infrared light at its resonant wavelength, respectively, realizing the integration of the functions of two optical devices at a subwavelength scale. In a specific preferred solution, the absorption rate of the device for x-polarized light at the resonant wavelength can reach 99.9%, and the y-polarized light can be reflected, playing the role of a high-performance linear polarizer.

[0012] The reason is that by adjusting the unit period of the metasurface, the absorption peak wavelength of x-polarized light can be continuously tuned in the near-infrared range, the average absorption rate of x-polarized light at the resonant wavelength exceeds 99%, and the reflectivity of y-polarized light is always maintained above 75% while maintaining the high absorption rate of x-polarized light. By immersing the metasurface in immersion liquids with different refractive indices, the absorption peak wavelength of the metasurface can be actively tuned: when the immersion liquids use deionized water, glycerol and liquid crystal respectively, the absorption peak wavelength can be continuously and actively switched in the near-infrared range, and at the resonant wavelength, the average absorption rate of x-polarized light exceeds 99.5%, and the reflectivity of y-polarized light is maintained above 76%.

[0013] In a third aspect, the present invention provides a design method for a bimetallic hybrid metasurface that realizes polarization-selective absorption and immersion-controllable liquid, characterized in that it comprises the following steps:

[0014] S1: Determine that the bimetallic hybrid metasurface structure is a bimetallic hybrid layer-silicon dioxide layer-silver reflective layer arranged in order from top to bottom;

[0015] S2: Simulate and calculate the reflection and absorption spectra of the bimetallic hybrid metasurface under different polarized light illumination;

[0016] S3: By changing the unit period, structural parameters, etc., study the variation of the optical properties of the metasurface and optimize the performance of the device under x and y polarized light;

[0017] S4: Immerse the metasurface in liquids with different refractive indices, simulate and calculate its optical performance under different immersion conditions, and verify the tunability and polarization selectivity of the absorption peak wavelength.

[0018] The advantages and beneficial effects of the present invention are as follows:

[0019] 1. The device of the present invention can exhibit completely different optical responses to x-polarized and y-polarized light at its resonant wavelength, achieving high-contrast infrared polarization-selective perfect absorption and reflection, effectively solving the problem of high-contrast polarization-dependent absorption being difficult to achieve in the prior art, and can be widely used in optical systems requiring precise polarization control.

[0020] 2. By changing the unit period or immersion strategy, the present invention can continuously tune the absorption peak wavelength of x-polarized light in the near-infrared band, providing flexible wavelength customization capabilities for optical applications in the near-infrared band and meeting the requirements of different application scenarios for specific working wavelengths.

[0021] 3. The dual-metal hybrid architecture of the present invention not only achieves excellent optical performance, but also avoids the difficulty of photolithography stripping caused by excessively thick metal layers. By rationally designing structural parameters, such as oxide layer thickness, metal thickness, and duty cycle, the optical performance of the metasurface is further optimized, so that it can maintain a stable and efficient absorption rate under different working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : is a schematic diagram of the structure of the liquid-adjustable infrared polarization-selective perfect absorption device based on the bimetallic hybrid metasurface of the present invention, the width of the aluminum nanoribbon is w1, the width of the titanium nanoribbon is w2, and P is the unit period of the bimetallic hybrid metasurface;

[0023] Figure 2 It is a reflectivity simulation diagram of the metasurface composed of a single metal or a double metal under different polarization conditions in the present invention.

[0024] Figure 3is a simulation diagram of the absorption performance of the bimetallic hybrid metasurface under different polarization conditions under normal incidence in an embodiment of the present invention;

[0025] Figure 4 is a simulation diagram of the absorption performance of the bimetallic hybrid metasurface when irradiated with x-polarized and y-polarized light at different periods in an embodiment of the present invention;

[0026] Figure 5 It is a simulation diagram of the absorption performance of the bimetallic hybrid metasurface under different refractive index liquid immersion conditions in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to more clearly illustrate the structure of the present invention and the functions it realizes, the present invention is further described below with reference to specific embodiments in conjunction with the accompanying drawings.

[0028] Example 1

[0029] This embodiment is a specific design process and performance characterization of a bimetallic hybrid metasurface that realizes polarization selective absorption and adjustable immersion. The bottom and middle layer thin film preparation process is to place a clean substrate in a vacuum coating system, and coat a 100nm silver layer and a 40nm silicon dioxide layer from bottom to top respectively; the top bimetallic hybrid layer preparation process is to perform coating-electron beam exposure-development-aluminum thermal evaporation-stripping on the above thin film structure, and then coating-electron beam exposure-development-titanium thermal evaporation-stripping.

[0030] As an embodiment, in order to more clearly illustrate the structural design and performance of the invention, specific dielectric and metal materials will be selected, and the structural parameters will be designed and optimized through electromagnetic field simulation software, and the performance of the device will be characterized.

[0031] Figure 1 This is a schematic diagram of the structure of the bimetallic hybrid metasurface that achieves polarization-selective absorption and immersion-adjustable liquid. At its resonant wavelength, the metasurface structure achieves 99.9% absorption of x-polarized incident light and reflects y-polarized incident light. The absorption and reflection behavior of the metasurface under different polarized light irradiation is clearly presented. The set thickness of the upper bimetallic hybrid layer is 35nm, the set thickness of the middle dielectric layer silicon dioxide is 40nm, and the set thickness of the bottom silver reflective layer is 100nm.

[0032] In order to illustrate and demonstrate the structural advantages of this bimetallic hybrid metasurface, we simulated and calculated the optical properties of the single metal metasurface and the bimetallic hybrid metasurface, such as Figure 2 As shown in Figure 2, compared with the single metal metasurface, the bimetallic hybrid metasurface exhibits an absorptivity of 99.9% at the resonant wavelength. The unit period of the single metal and bimetallic hybrid metasurfaces is 600nm.

[0033] When the unit period of the bimetallic hybrid metasurface is set to 400 nm, the simulated spectrum is as follows Figure 3 As shown in the figure, under the designed dual-metal hybrid metasurface structure, the structure intuitively reflects the difference in absorption performance under x-polarized and y-polarized light, and has a peak near 1400nm. When irradiated with x-polarized light, due to the strong resonance between the titanium and aluminum nanoribbons, the light field is highly localized in the gap between the nanoribbons, and the energy is strongly absorbed, with an absorption rate of up to 99.9%, thus achieving perfect absorption function. Under y-polarized light irradiation, most of the light is directly reflected by the bottom silver layer with a high reflectivity, enabling the metasurface to reflect y-polarized light like a mirror, that is, the design also satisfies the function of a high-performance linear polarizer.

[0034] Keeping the thickness of the upper aluminum / titanium layer, the thickness of the middle silicon dioxide layer, and the thickness of the bottom silver layer unchanged, changing the period P, and adjusting the unit period P, the optical resonance characteristics of the metasurface can be effectively changed. Figure 4 As shown in the figure, when the period P changes from 140nm to 800nm, the absorption peak wavelength of x-polarized light will undergo a significant red shift, changing continuously from 1200nm to 1850nm, and the average absorption rate is always greater than 99% during this process. At the same time, the reflectivity of y-polarized light at the corresponding resonant wavelength remains above 75%, which makes it possible to achieve the tuning of the absorption peak wavelength of x-polarized light without affecting the reflection characteristics of y-polarized light, thus maintaining the polarization selection performance of the overall structure.

[0035] Figure 5 In order to utilize the liquid immersion tuning strategy, the continuous active tuning of the absorption peak wavelength of the bimetallic hybrid metasurface is realized. Specifically, the metasurface is immersed in liquids with different refractive indices for testing. The principle is that when the refractive index of the liquid changes, the propagation characteristics of light at the interface between the metasurface and the liquid change, thereby affecting the optical resonance of the metasurface. For example, when common substances such as deionized water (n1=1.33), glycerol (n2=1.475) and liquid crystal (n3=1.9) are used as immersion liquids, the absorption peak wavelength of the bimetallic hybrid metasurface can be continuously and actively switched between 1385nm and 2150nm, and the average absorption rate exceeds 99.5%. During the entire liquid tuning process, the reflection of y-polarized light can still be maintained at more than 76%, ensuring that the metasurface can still maintain the performance stability of the linear polarizer under different liquid immersion.

[0036] The liquid-adjustable infrared polarization selective absorption device based on the bimetallic hybrid metasurface designed in the present invention and the proposed bimetallic hybrid metasurface structure can be replaced by other drawings according to these drawings and materials by ordinary technicians in this field without any creative work.

Claims

1. A bimetallic hybrid metasurface, characterized in that: a metal layer, located at the bottom; an insulating layer formed on the metal layer; as well as A bimetallic hybrid layer is formed on the insulating layer, and the bimetallic hybrid layer consists of a first metal nanobelt and a second metal nanobelt, wherein the first metal nanobelt and the second metal nanobelt both extend infinitely along the y-axis, and the first metal nanobelt and the second metal nanobelt are periodically arranged along the x-axis.

2. The bimetallic hybrid metasurface according to claim 1, characterized in that: The first metal nanobelt is a titanium nanobelt; the second metal nanobelt is an aluminum nanobelt.

3. The bimetallic hybrid metasurface according to claim 2, characterized in that: The metal layer is a silver layer with a thickness of 100-120nm.

4. The bimetallic hybrid metasurface according to claim 3, characterized in that: The material of the insulating layer is any one of silicon dioxide, aluminum oxide or organic glass.

5. A liquid adjustable infrared polarization selective absorption device, characterized in that: It comprises the bimetallic hybrid metasurface as described in claim 4.

6. The adjustable infrared polarization selective absorption device according to claim 5, characterized in that: At the resonance wavelength, the device has an absorption rate of more than 99% for x-polarized light and reflects y-polarized light, thus playing the role of a high-performance linear polarizer.

7. The adjustable infrared polarization selective absorption device according to claim 6, characterized in that: By adjusting the unit period of the metasurface, the absorption peak wavelength of x-polarized light can be continuously tuned in the near-infrared range. The absorption rate of x-polarized light at the resonant wavelength exceeds 99%, and while maintaining the high absorption rate of x-polarized light, the reflectivity of y-polarized light is always maintained above 75%.

8. The adjustable infrared polarization selective absorption device according to claim 7, characterized in that: By immersing the metasurface in immersion liquids with different refractive indices, the absorption peak wavelength of the metasurface can be actively tuned.

9. The adjustable infrared polarization selective absorption device according to claim 8, characterized in that: When the immersion liquids are deionized water, glycerol and liquid crystal respectively, the absorption peak wavelength can be continuously and actively switched in the near-infrared range. At the resonance wavelength, the absorptivity of x-polarized light exceeds 99%, and the reflectivity of y-polarized light remains above 76%.

10. A liquid-tunable infrared polarization selective absorption method based on a bimetallic hybrid metasurface, characterized in that: The method of claim 4 based on a bimetallic hybrid metasurface comprises the following steps: S1: Determine that the bimetallic hybrid metasurface structure is arranged in order from top to bottom: bimetallic hybrid layer-insulating layer-metal layer; S2: Simulate and calculate the reflection and absorption spectra of the bimetallic hybrid metasurface under different polarized light illumination; S3: By changing the unit period and structural parameters, the optical performance of the metasurface is studied to optimize the performance of the device under x and y polarized light; S4: Immerse the metasurface in liquids with different refractive indices, simulate and calculate its optical performance under different immersion conditions, and verify the tunability and polarization selectivity of the absorption peak wavelength.

Citation Information

Patent Citations

  • Asymmetric electromagnetic wave separator based on binary meta-structure surface

    CN111665582A

  • Sub-wavelength grating polarizer based on metal and medium mixed sandwich structure

    CN118465907A

  • Optical fiber refractive index sensor with cross grating

    CN217112073U

  • Transmission-type color filter of bimetallic grating nanometer microcavity

    CN222028447U

  • Sub-wavelength structures, devices and methods for light control in material composites

    US20140332077A1